Impacting Nursing Students' Confidence and Skills in Utilizing Continuous Glucose Monitoring Devices. - George, Tracy; Phillips, Tiffany A.; Munn, Allison C.; Bennett, Meagan (Online Journal of Rural Nursing & Health Care, 2026)
Purpose: Continuous glucose monitoring (CGM) provides a more reliable and convenient way for patients to check blood glucose levels than fingerstick monitoring. Patients in rural areas may have less access to CGMs than those in urban areas. The purpose of this project was to provide focused education about CGMs and a two-week user-wear experience to undergraduate nursing and family nurse practitioner (FNP) students in a rural liberal arts university through an intraprofessional workshop and user-wear experience. Sample: Students eligible for participation in the study included those in the graduate FNP (n=16) and undergraduate pre-licensure Bachelor of Science in nursing (BSN) (n=35) programs. Methods: All eligible FNP and BSN students (n=51) participated in the in-person educational session on CGMs. At the beginning of the CGM workshop, students were asked to complete the pre-implementation survey. During the workshop, students and faculty were educated about CGMs and given the opportunity to self-apply a CGM for a two-week user-wear experience. At the end of the user-wear experience, students were encouraged to complete the post-implementation survey. Findings: All 10 scored survey items measuring student familiarity and perception of skill with CGM devices had statistically significant differences in pre- and post-survey ranked scores. Review of the qualitative responses revealed four themes: understanding, confidence, personal experience, and clinical preparation. Conclusions: The intraprofessional CGM workshop and user wear experience allowed undergraduate BSN and graduate FNP students to engage with each other in a clinical and experiential learning activity to improve their understanding, confidence, and skills in diabetes management with CGM devices. All students reported improved self-perception of confidence and skills in using CGMs after the workshop. It is crucial for undergraduate and nurse practitioner students to become more familiar with CGMs through workshops and hands-on activities, especially in rural areas where CGM use is not optimized.